Effects of drying temperature and solvent concentration on the separation properties of polyamide 6 membrane / Kamil, R.N.M …[et al.] - Kamil, R.N.M; F., Shamsuddin; Z., Man; N.Y, Yuhana (2006)
The effects of drying temperature and solvent concentration on the separation properties of polyamide 6 membrane were investigated In this study, polyamide 6 membranes were prepared by casting 10-20 wt% solution of polymer in 85 wt% formic acid onto a glass plate and precipitation in water. The membranes prepared were dried for 1 hour at different temperatures ranging from 40 to 130°C The separation properties of the membranes were studied with binary water-ethanol mixtures consisting of 40 wt% ethanol. The drying temperature as well as the solvent concentration of PA 6 solution influenced the separation properties of PA 6 membrane. The separation of ethanol from water was optimum using membrane which was dried at 70°C However, as the drying temperature increased, the extraction of ethanol decreased due to reduction in pore size. Similarly, as the solvent concentration decreased, the ethanol separation also decreased as a result of smaller pore size. These effects were confirmed by SEM micrographs.